FINANCIAL LITERACY LEADS TO DEVELOPMENT: MEDIATING ROLE OF FINANCIAL INCLUSION, AN EMPIRICAL STUDY (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The study is performed with the major objective  of gaining insights and knowledge about the  role and importance of financial inclusion  in the holistic development of a nation. The  study also laid emphasis in finding the role of  social capital as a moderator in the relationship  between financial literacy and financial inclusion  and impact of mobile banking as a moderator  in the relationship between financial inclusion  and development through mobile banking.  Mediating role of Financial Inclusion was also  explored in the study. The study is empirical  in nature. The sample size of the study is 197  respondents which were chosen through non  probabilistic convenient sampling method. The  study uses structural equation modeling approach  to find the association between financial literacy  and financial inclusion and development. The  study also performs hierarchical regression to  check the moderation effect and Process Macro  for mediation analysis. The research finds that  there exists positive significant association  between the level of penetration of the financial  literacy and the extent of financial inclusion  and between the prevailing level of financial  inclusion and the level of nation’s development.  It was also concluded from the study that  mobile banking significantly act as a moderator  for the relationship between financial literacy  and financial inclusion and social capital was  a significant moderator for the relationship  between financial inclusion and development  of the nation. Financial Inclusion partially  mediates the relationship between financial  literacy and development of the nation. Since  the study is performed only on a sample of  197, belonging to Delhi NCR region, it can  be taken as a limitation for the study.In future,  the significance of demographic variables on the  established relationship can be explored.
Keywords: objective; relationship; future